2018
DOI: 10.1016/j.ajog.2017.11.575
|View full text |Cite
|
Sign up to set email alerts
|

A placenta clinic approach to the diagnosis and management of fetal growth restriction

Abstract: Effective detection and management of fetal growth restriction is relevant to all obstetric care providers. Models of best practice to care for these patients and their families continue to evolve. Since much of the disease burden in fetal growth restriction originates in the placenta, the concept of a multidisciplinary placenta clinic program, managed primarily within a maternal-fetal medicine division, has gained popularity. In this context, fetal growth restriction is merely one of many placenta-related dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
80
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 127 publications
2
80
0
3
Order By: Relevance
“…[1][2][3][4][5][6] However, given the difficulty in determining the growth potential of the individual fetus, FGR is commonly defined as sonographic estimated fetal weight or abdominal circumference below the 10th percentile for gestational age. 1,8,[10][11][12][13][14][15][16][17][18][19][20] The most common placental findings in pregnancies complicated by FGR are lesions reflective of maternal vascular malperfusion (MVM) pathology, although other pathologies such as fetal vascular malperfusion and chronic villitis have been associated with FGR as well. 1,8,[10][11][12][13][14][15][16][17][18][19][20] The most common placental findings in pregnancies complicated by FGR are lesions reflective of maternal vascular malperfusion (MVM) pathology, although other pathologies such as fetal vascular malperfusion and chronic villitis have been associated with FGR as well.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6] However, given the difficulty in determining the growth potential of the individual fetus, FGR is commonly defined as sonographic estimated fetal weight or abdominal circumference below the 10th percentile for gestational age. 1,8,[10][11][12][13][14][15][16][17][18][19][20] The most common placental findings in pregnancies complicated by FGR are lesions reflective of maternal vascular malperfusion (MVM) pathology, although other pathologies such as fetal vascular malperfusion and chronic villitis have been associated with FGR as well. 1,8,[10][11][12][13][14][15][16][17][18][19][20] The most common placental findings in pregnancies complicated by FGR are lesions reflective of maternal vascular malperfusion (MVM) pathology, although other pathologies such as fetal vascular malperfusion and chronic villitis have been associated with FGR as well.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Placental dysfunction is the most common etiology of FGR. 10,11,13,15,16,[20][21][22] In recent years, it has been suggested that early and late FGR may represent two distinct entities. 10,11,13,15,16,[20][21][22] In recent years, it has been suggested that early and late FGR may represent two distinct entities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations